NDSHA - The New Paradigm for RSHA - An Updated Review - Bela, J.; Panza, G. F. (Vietnam Journal of Earth Sciences, 2021)
A New Paradigm (data driven and not like the currently model driven) is needed for Reliable Seismic Hazard Assessment RSHA. Neo-Deterministic Seismic Hazard Assessment (NDSHA) integrates earthquake geology, earthquake science, and particularly earthquake physics to finally achieve a New (and needed) Paradigm for Reliable Seismic Hazard Assessment RSHA. Although observations from many recent destructive earthquakes have all confirmed the validity of NDSHA’s approach and application to earthquake hazard forecasting-nonetheless damaging earthquakes still cannot yet be predicted with a precision requirement consistent with issuing a red alert and evacuation order to protect civil populations. However, intermediate-term (time scale) and middle-range (space scale) predictions of main shocks above a pre-assigned threshold may be properly used for the implementation of low-key preventive safety actions, as recommended by UNESCO in 1997. Furthermore, a proper integration of both seismological and geodetic information has been shown to also reliably contribute to a reduction of the geographic extent of alarms and it therefore defines a New Paradigm for TimeDependent Hazard Scenarios: Intermediate-Term (time scale) and Narrow-Range (space scale) Earthquake Prediction.